Protective Intranasal Immunization Against Influenza Virus in Infant Mice Is Dependent on IL-6 - Bonney, Elizabeth Ann; Krebs, Kendall; Kim, Jihye; Prakash, Kirtika; Torrance, Blake L.; Haynes, Laura; Rincon, Mercedes (Frontiers in Immunology, 2020)
Respiratory diseases adversely affect infants and are the focus of efforts to develop vaccinations and other modalities to prevent disease. The infant immune system differs from that of older children and adults in many ways that are as yet ill understood. We have used a C57BL/6 mouse model of infection with a laboratory- adapted strain of influenza (PR8) to delineate the importance of the cytokine IL-6 in the innate response to primary infection, and the development of protective immunity in adult mice. Herein, we used this same model in infant (14 days of age) mice to determine the effect of IL-6 deficiency. Infant wild type mice are more susceptible than older mice to infection, similar to the findings in humans. IL-6 is expressed in the lung in the early response to PR8 infection. While intramuscular immunization does not protect against lethal challenge, intranasal administration of inactivated virus is protective and correlates with expression of IL-6 in the lung, activation of lung CD8 cells, and development of an influenza-specific antibody response. In IL-6 deficient mice, this response is abrogated, and deficient mice are not protected against lethal challenge. These studies support the importance of the role of the tissue environment in infant immunity, and further suggest that IL-6 may be helpful in the generation of protective immune responses in infants.